2000
DOI: 10.1046/j.1365-294x.2000.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence between Atlantic and Indo‐Pacific stocks of bigeye tuna (Thunnus obesus) and admixture around South Africa

Abstract: Two mitochondrial DNA segments of the bigeye tuna (Thunnus obesus) were amplified by polymerase chain reaction (PCR), and restriction fragment length polymorphism (RFLP) analyses of these segments were used for the genetic stock study. The variation in a segment flanking the ATPase and COIII genes was low; only two genotypes (alpha and beta) were detected by RsaI digestion. Yet a large difference in the genotype distribution was observed between ocean basin samples. The alpha type predominated in four Atlantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
3
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 17 publications
8
77
3
4
Order By: Relevance
“…This differentiation is supported by the highly significant heterogeneity found between the Atlantic and Pacific populations in a recent RFLP analysis on the mitochondrial ATPase gene (Chow & Ushiama 1995), and a similar pattern is also found in cogeneric bigeye tuna (Chow et al 2000) and other large pelagic fishes such as the swordfish (AlvaradoBremer et al 1999). Blood group analyses are consistent with this differentiation.…”
Section: Discussionmentioning
confidence: 67%
“…This differentiation is supported by the highly significant heterogeneity found between the Atlantic and Pacific populations in a recent RFLP analysis on the mitochondrial ATPase gene (Chow & Ushiama 1995), and a similar pattern is also found in cogeneric bigeye tuna (Chow et al 2000) and other large pelagic fishes such as the swordfish (AlvaradoBremer et al 1999). Blood group analyses are consistent with this differentiation.…”
Section: Discussionmentioning
confidence: 67%
“…In other tuna species DNA studies have revealed little intra-specific divergence within, but significant divergence between ocean basins. In bigeye tuna (T. obesus) DNA markers showed no divergence among population samples from the western Pacific Ocean (Chiang et al, 2006), but high divergence among Atlantic and Indo-Pacific populations (Chow et al, 2000;Chiang et al, 2006;Martinez et al, 2006). Similarly, in albacore tuna (T. alalunga) no genetic differences were detected among samples from the Northwest Pacific Ocean (Wu et al, 2009), but significant differences were reported among Atlantic and Indo-Pacific populations (Vinas et al, 2004).…”
Section: Intraspecific Divergencementioning
confidence: 99%
“…In particular, genetic differentiation is low between tuna populations within and between oceans (Alvarado Bremer et al, 1998;Gerwe and Hampton, 1998;Chow et al, 2000;Appleyard et al, 2002;Durand et al, 2005) because of the occurrence of continuous, circumtropical pelagic environment and a wide range of suitable spawning grounds. Kawakawa is widely distributed in the tropical and subtropical waters of the Indo-Pacific region and was observed to spawn in waters of Hong Kong, India, Thailand, and Philippines (Yesaki, 1994).…”
Section: Discussionmentioning
confidence: 99%